METHODS AND MEANS OF MONITORING THE FUNCTIONING OF WEB SERVICES - ANDRUSYAK, IVANNA; SEVERYNENKO, DANYLO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper explores the development of methods and tools for automated monitoring systems to ensure the reliable operation of web services. In today’s digital landscape, where a large portion of business and communication depends on stable web services, ensuring their reliability and performance is critical. This research highlights the need for a robust automated monitoring system capable of real-time fault detection to address issues promptly, enhance service reliability, and improve user satisfaction. The paper evaluates existing monitoring solutions such as Datadog, New Relic, Dynatrace, and Uptime Robot, analyzing their capabilities, strengths, and limitations. These tools are essential for monitoring IT infrastructure and applications, offering features such as real-time data analysis, automated alerts, and integration across various programming frameworks. However, challenges like high implementation costs and system complexity underscore the need for scalable, customizable solutions, especially for small and medium-sized businesses. Additionally, the authors present a framework for web service monitoring that emphasizes automation through the use of specialized browser management tools, which convert program commands into browser actions. The framework incorporates a class-based page design to facilitate modular testing and streamline maintenance. Report generation after testing is another key component, providing valuable insights through metrics such as test duration and error frequency. Integrating these systems into continuous integration environments is achieved through tools like Jenkins for remote script execution, Allure for structured reporting, and Docker for flexible environment deployment. This architecture ensures seamless, automated testing, efficient data analysis, and optimized resource allocation, helping address technical and operational challenges. The findings provide a practical guide for developing automated monitoring systems, contributing to improved stability and efficiency of web services in a fast-evolving digital world.